The mediating effect of self-perceived aging on social capital and depression among Chinese community-dwelling older adult: a cross-sectional study - Ye, Yuguo; Liu, Hui; Wang, Ziming; Zhang, Qianwei; Yang, Shifan; Yang, Lian (Frontiers in Public Health, 2025)
BackgroundAmid an aging society, boosting older adult social capital is crucial to meet their growing health needs. This could be an effective way to alleviate the shortage of public health resources and improve the mental health of the older adult. However, the underlying mediation pathways of how social capital affects the mental health of the older adult are not yet clear. This study aims to explore whether social capital has an impact on the depression levels of community-dwelling older adult and whether self-perceived aging mediates the relationship between social capital and depression, while providing a theoretical basis for scientifically constructing mental health intervention programs for the older adult.MethodA cross-sectional study was conducted from June to December 2022 in Chengdu, China. A stratified sampling survey of 1809 community-dwelling older adult individuals was conducted. Data on sociodemographic characteristics, social capital, self-perceived aging, and depression were collected. Univariate analysis was used to compare the depression differences among community-dwelling older adult with different sociodemographic characteristics. Pearson correlation analysis was used to explore the correlations between social capital, self-perceived aging, and depression. The SPSS PROCESS macro program was used to test the mediating effect of self-perceived aging between social capital and depression.ResultsThe mean score of depression was 39.07 (SD 13.97). Univariate analysis showed that there were statistically significant differences in depression scores among community-dwelling older adult of different age, marital status, chronic disease, medical insurance, endowment insurance, and monthly income per capita (p < 0.05). Social capital is negatively correlated with self-perceived aging (r = −0.418, p < 0.001) and also negatively correlated with depression (r = −0.263, p < 0.001), while self-perceived aging is positively correlated with depression (r = 0.324, p < 0.001). Social capital was negatively correlated with depression (β = −0.477, p < 0.001), and self-perceived aging partially mediated the relationship between social capital and depression, with a mediating effect of −0.180 (95% bootstrap CI −0.225 −0.139), accounting for 37.7% of the total effect.ConclusionSelf-perceived aging played a partial mediating role between social capital and depression. It is recommended that relevant management agencies, communities, and families take effective measures to enhance the social capital of the older adult, help them build a positive self-perceived aging, and thereby reduce the risk of depression.